2020
DOI: 10.1002/jcsm.12508
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of sarcopenia in very old patients with hip fracture

Abstract: Background Hip fracture is both a cause and a consequence of sarcopenia. Older persons with sarcopenia have an increased risk of falling, and the prevalence of sarcopenia may be increased in those who suffer a hip fracture. The aim of this study was to explore potential biomarkers (neuromuscular and peripheral pro-inflammatory and oxidative stress markers) that may be associated with sarcopenia in very old persons with hip fracture. Methods We recruited 150 consecutive patients ≥80 years old admitted to an ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 58 publications
1
22
1
2
Order By: Relevance
“…Por otro lado, las evidencias sobre los biomarcadores para la sarcopenia son todavía escasas; se sabe que no hay un único biomarcador ideal, sino que se debería disponer de un panel de herramientas complementarias como las imágenes diagnósticas, los biomarcadores séricos y las pruebas funcionales para su diagnóstico (37).…”
Section: Sarcopenia Y Albúmina En El Adulto Mayorunclassified
See 1 more Smart Citation
“…Por otro lado, las evidencias sobre los biomarcadores para la sarcopenia son todavía escasas; se sabe que no hay un único biomarcador ideal, sino que se debería disponer de un panel de herramientas complementarias como las imágenes diagnósticas, los biomarcadores séricos y las pruebas funcionales para su diagnóstico (37).…”
Section: Sarcopenia Y Albúmina En El Adulto Mayorunclassified
“…También, se ha evidenciado que el fragmento C-terminal de la agrina (CAF) aumenta en pacientes con fractura de cadera cuando hay sarcopenia (37). Asimismo, se ha estudiado la creatinina como metabolito para estimar la masa osteomuscular; sin embargo, los resultados de la creatinina urinaria varían de 11 a 30 %, dependiendo del tipo de dieta (39).…”
Section: Sarcopenia Y Albúmina En El Adulto Mayorunclassified
“…A cross-sectional study exploring neuromuscular, peripheral pro‐inflammatory, and oxidative stress molecules as potential biomarkers associated with sarcopenia in old-aged people with hip fracture only found differences in peripheral TNF‐α levels and catalase activity. Probably, TNF‐α and catalase are markers of an early inflammatory reaction that is impaired in subjects with sarcopenia [ 12 ].…”
Section: Sarcopenia and Immuno-mediated Rheumatic Diseasesmentioning
confidence: 99%
“… 7 Sarcopenia is associated with four times increased rate of fragility fracture 8 with the presentation of poorer balancing abilities and substantial increase in fall risks, thus making sarcopenia a highly predictive factor of fragility fracture in elderly. 9 A recent study in Europe also revealed that prevalence of sarcopenia in hip fracture patients is as high as 74% of men and 54% of women, 10 making sarco‐osteoporotic fracture a newly emerging geriatric condition. 11 …”
Section: Introductionmentioning
confidence: 99%